2014
DOI: 10.1080/10826068.2013.877030
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Separation of Caseins from Milk by Phosphates Precipitation

Abstract: Milk protein of farm animals is difficult to isolate because of the presence of casein micelles, which are hard to separate from whey by using centrifugation or filtration. Insoluble casein micelles also create an obstacle for purification instruments to operate efficiently. The conventional method, to precipitate caseins by lowering pH to 4.6 and then recover the whey fraction for further purification using chromatography techniques, is not applicable to proteins having an isoelectric point similar to caseins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…However, because zinc ion induces hGH dimerization [41], this process could not be utilized in our study. Moreover, experiments using calcium phosphate particles (CAP) [42], citric acid [43], and sodium phosphate [44] were explored for casein removal from the milk of transgenic animals; however, casein was not completely removed. After several trials and various experiments, we established the pretreatment process outlined in Fig 2B. Nevertheless, there were substantial impurities remaining after the process, including rhGH fragments digested by tryptic peptidases [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…However, because zinc ion induces hGH dimerization [41], this process could not be utilized in our study. Moreover, experiments using calcium phosphate particles (CAP) [42], citric acid [43], and sodium phosphate [44] were explored for casein removal from the milk of transgenic animals; however, casein was not completely removed. After several trials and various experiments, we established the pretreatment process outlined in Fig 2B. Nevertheless, there were substantial impurities remaining after the process, including rhGH fragments digested by tryptic peptidases [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…This justifies that such strategy cannot be retained in the present case. As an alternative, a study reported the use of a phosphate buffer (1M; pH 6.0) to eliminate most of the caseins instead of using hydrochloric acid in the objective of extracting recombinant human factor IX (rhFIX) and recombinant hirudin (rH) in milk, which allowed a whey protein fraction containing more than 90% recovery for both recombinant hormones [72]. This approach could be tested to overcome the challenge associated to the extraction of rbGH from the micellar network formed by caseins.…”
Section: Prospects For Efficient Analysis Of Rbgh In Milkmentioning
confidence: 99%
“…It is tasteless, odorless with isoelectric pH 4.6 [14,15]. In milk, calcium phosphate and casein form colloidal particles called casein micelles [7,16]. The richest profile of amino acids present in the casein shows that it is a valuable source of energy for the development of the brain and the strengthening of muscles and bones [17].…”
Section: Introductionmentioning
confidence: 99%